2019
DOI: 10.1016/s2214-109x(19)30439-5
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the potential impact and cost-effectiveness of rotavirus vaccination in 73 Gavi countries: a modelling study

Abstract: Background Previous studies have found rotavirus vaccination to be highly cost-effective in low-income countries. However, updated evidence is now available for several inputs (ie, rotavirus disease mortality rates, rotavirus age distributions, vaccine timeliness, and vaccine efficacy by duration of follow-up), new rotavirus vaccines have entered the market, vaccine prices have decreased, and cost-effectiveness thresholds have been re-examined. We aimed to provide updated cost-effectiveness estimates to inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…Despite the differences in underlying model and the assumptions, our estimates are similar to the estimates of RSV MI impact in LMIC settings. Our results are also comparable with the projected impact of rotavirus vaccines, for instance, which are predicted to avert 36% of rotavirus-related diarrheal deaths among under 5 children across Gavi countries [30] . While the scale of RSV impact is smaller than that for other blockbuster vaccines, this is expected given the relative burden [31] .…”
Section: Discussionsupporting
confidence: 80%
“…Despite the differences in underlying model and the assumptions, our estimates are similar to the estimates of RSV MI impact in LMIC settings. Our results are also comparable with the projected impact of rotavirus vaccines, for instance, which are predicted to avert 36% of rotavirus-related diarrheal deaths among under 5 children across Gavi countries [30] . While the scale of RSV impact is smaller than that for other blockbuster vaccines, this is expected given the relative burden [31] .…”
Section: Discussionsupporting
confidence: 80%
“…We used UNIVAC (version 1.4.09), an Excel-based, deterministic proportionate outcomes model that has been used extensively for country-specific and global analyses. 6 , 14 , 17 , 18 , 19 , 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…Methods for estimating rotavirus disease burden have been described in detail elsewhere. 6 , 14 The full list of country-specific data inputs and uncertainty ranges used to model disease burden is available in the appendix (pp 2–5 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, ninety-nine countries have introduced the vaccine, including 73 Gavi-eligible countries [14]. Rotavirus vaccination has the potential to prevent nearly 600 000 deaths and to save approximately $484•1 million from the government perspective and $878•0 million from the societal perspective [15]. A recent systematic review (2019) on rotavirus vaccines showed evidence of the vaccine's effectiveness in preventing death caused by rotavirus diseases and vaccine safety, both in developed and developing countries [16].…”
Section: Introductionmentioning
confidence: 99%